Papaver Plants: Current Insights on Phytochemical and Nutritional Composition Along with Biotechnological Applications. (3rd February 2022) - Butnariu, Monica; Quispe, Cristina; Herrera-Bravo, Jesús; Pentea, Marius; Sarac, Ioan; Küşümler, Aylin Seylam; Özçelik, Beraat; Painuli, Sakshi; Semwal, Prabhakar; Imran, Muhammad; Gondal, Tanweer Aslam; Emamzadeh-Yazdi, Simin; et al.
Abstract : The genus Papaver is highly esteemed in the pharmacy industry, in the culinary field, and as ornamental plants. These plants are also valued in traditional medicine. Among all Papaver species, Papaver somniferum L. (opium poppy) is the most important species in supplying phytochemicals for the formulation of drugs, mainly alkaloids like morphine, codeine, rhoeadine, thebaine, and papaverine. In addition, Papaver plants present other types of phytochemicals, which altogether are responsible for its biological activities. Therefore, this review covers the phytochemical composition of Papave r plants, including alkaloids, phenolic compounds, and essential oils. The traditional uses are reviewed along with their pharmacological activities. Moreover, safety aspects are reported to provide a deep overview of the pharmacology potential of this genus. An updated search was carried out in databases such as Google Scholar, ScienceDirect, and PubMed to retrieve the information. Overall, this genus is a rich source of alkaloids of different types and also contains interesting phenolic compounds, such as anthocyanins, flavonols, and the characteristic indole derivatives nudicaulins. Among other pharmacological properties, numerous preclinical studies have been published about the analgesic, anticancer, antimicrobial, antioxidant, and antidiabetic activities of Papaver plants. Although it highlights the significant impact of this genus for the treatment of a variety of diseases and conditions, as a future prospect, characterization works accompanying preclinical studies are required along with clinical and toxicology studies to establish a correlation between the scientific and traditional knowledge.